SIKAP DAN STATUS EKONOMI DENGAN PERNIKAHAN DINI PADA REMAJA PUTRI - Kumaidi Kumaidi; Yuliati Amperaningsih (Politeknik Kesehatan Tanjung Karang, 2014)
Kumaidi1)Yuliati Amperaningsih1) 1)Jurusan Keperawatan Poltekkes Kemenkes Tanjungkarang Abstract: Attitude and ekonomics status with early marriage in young women. Teens is a period of growing a person in the transition of children into adolescent. Data recording Systems and Reporting Integrated Public Health Center (SP2TP) Karta Raharja in 2012, the amount of adolescent who married early (16 years by 62 people 40%) 0f the 155 total wedding and increased in 2013 by 74 people (45,7%) of the 162 total wedding. Early marriage in public helath center of Karta Raharja in 2012 by 39people (29,1%) of the 134 total wedding and in 2013 by 35 people (24,6%) of the 142 total wedding. The purpose of research was to determine the relationship of attitudes and economics status of families with early marriage in young women in the working are public health of Karta Raharja wets Tulang Bawang in 2014. Design of research used analytic with cross sectional approach. The population of young women in public health center Karta Raharja, West Tulang Bawang regency totaling 784 people, sample of 89 people. Sample stratified Random Sampling Tecnique. Data analysis using the chi square. The result of chi square obtained her are relationship with the attitude of early marriage on young women (p-value = 0,004 < 0,05). There are relation ship of the economnics status with early marriage in young women. Based on the research results sugested to Public Health Center Karta Raharja, West Tulang Bawang Regency can socialize wedding time and the impact of early marriage in young women through counseling and the used language the is easily understanable to children who entered the young women and parrents, especially mother, and provide sklill in adolescent so that us could be work and cooperate with PNPM to provide capital.Keywords : Attitude, Economic, Early Marriage.Abstrak: Sikap dan Status Ekonomi dengan Pernikahan Dini pada Remaja Putri. Remaja merupakan suatu periode atau masa tumbuhnya seseorang dalam masa transisi dari anak-anak ke masa dewasa. Data Sistem Pencatatan dan Pelaporan Terpadu Puskesmas (SP2TP) Karta Raharja tahun 2012 jumlah remaja yang menikah dini <16 tahun sebesar 62 orang (40%) dari 155 total pernikahan dan meningkat di tahun 2013 menjadi sebesar 74 orang (45,7%) dari 162 total pernikahan. Pernikahan dini di wilayah kerja Puskesmas Karta Raharja tahun 2012 sebesar 39 orang (29,1%) dari 134 total pernikahan dan pada tahun 2013 sebesar 35 orang (24,6%) dari 142 total pernikahan. Tujuan penelitian adalah diketahui hubungan sikap dan status ekonomi keluarga dengan pernikahan dini pada remaja putri di Wilayah kerja Puskesmas Karta Raharja Kabupaten Tulang Bawang Barat tahun 2014. Desain penelitian yang digunakan analitik dengan pendekatan cross sectional. Populasi adalah seluruh remaja putri di Wilayah Kerja Puskesmas Karta Raharja Kabupaten Tulang Bawang Barat yang berjumlah 784 orang. Sampel sebesar 89 orang. Teknik sampel stratified random sampling. Analisis data menggunakan uji chi squre. Hasil uji Chi square didapat ada hubungan sikap dengan pernikahan dini pada remaja putri (p-value=0,004 < 0,05), ada hubungan status ekonomi keluarga dengan pernikahan dini putri (p-value=0,002 < 0,05). Diharapkan Puskesmas Karta Raharja Kabupaten Tulang Bawang Barat dengan mensosialisasikan waktu pernikahan dan dampak pernikahan dini melalui penyuluhan dan menggunakan bahasa yang mudah dipahami kepada anak yang memasuki usia remaja putri dan orang tua terutama ibu, serta memberikan keterampilan pada remaja agar remaja dapat bekerja dan dapat bekerjasama dengan PNPM untuk memberikan modal. Kata kunci: Sikap, Ekonomi, Pernikahan Dini